2020
DOI: 10.12998/wjcc.v8.i21.5284
|View full text |Cite
|
Sign up to set email alerts
|

Anterior bone loss after cervical disc replacement: A systematic review

Abstract: BACKGROUND Anterior bone loss (ABL) is a relatively easily neglected condition after cervical disc replacement (CDR). Whether this phenomenon is a radiological anomaly or a complication remains controversial. Several studies have reported the clinical characteristics of ABL and speculated on the pathogenic mechanism based on a certain type of artificial disc, while the overall understanding of ABL is lacking. AIM To describe the prevalence, impacts, and risk factors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Implant-related complications such as hypermobility, HO, implant subsidence or migration, vertebral osteolysis or anterior bone loss, vertebral fracture, or local kyphosis are serious complications that must be avoided. 41,42,[61][62][63][64][65][66] HO is one of the most common complications following ACDR. Although its risk factors are unclear, HO after ACDR causes a reduction in ROM at the indexed level after ACDR.…”
Section: Acdr-specific Complicationsmentioning
confidence: 99%
“…Implant-related complications such as hypermobility, HO, implant subsidence or migration, vertebral osteolysis or anterior bone loss, vertebral fracture, or local kyphosis are serious complications that must be avoided. 41,42,[61][62][63][64][65][66] HO is one of the most common complications following ACDR. Although its risk factors are unclear, HO after ACDR causes a reduction in ROM at the indexed level after ACDR.…”
Section: Acdr-specific Complicationsmentioning
confidence: 99%
“…Wang et al performed a systematic review of six studies including 440 patients who underwent CDR across 536 segments. They found that patients with BL achieved similar clinical outcomes compared with those without BL [ 32 ]. Wu et al performed a retrospective study of 396 patients in a single center and found BL did not affect clinical outcomes but patients with BL had a larger segmental ROM [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although short-term clinical results reported for Discocerv cervical disc were encouraging (Ramadan et al, 2007;Enan et al, 2011;Ling and Tiruchelvarayan, 2015), some concerns were reported such as anterior bone loss (Wang et al, 2020) and alumina head fracture (Nguyen et al, 2011). Moreover, the studies listed are relatively small in number of patients and duration in vivo compared with other cervical discs, for example (Zigler et al, 2020).…”
Section: Introductionmentioning
confidence: 99%